The impact of marketing mix and TAM on purchase intention through point of sale machine arbitrated by attitude and social engineering - Binte-Saif, Samira (BOHR International Journal of Finance and Market Research, 2025)
In Bangladesh, 57% respondents reported an increase of 20% or more in their creativity due to mobile devices and technology, while 26% indicated a rise of over 50%. When asked about the positive influence of mobile devices and technology on career and skills development, 69% of Bangladeshi respondents reported significant advancements. In terms of gender-based inputs, 73% of women and 67% of men agreed they had gained remarkable advancement in their careers and skills development through technology. The people of Bangladesh are quick to adopt new technology. The use of point of sale (POS) machines has increased rapidly, primarily due to convenience offered by the internet. Most supermarket owners now use POS machine, as they save labor cost and enhance customer safety. This paper focuses on a sample taken from three major cities of Bangladesh: Dhaka, Chattogram, Rajshahi. Research data analyses were conducted using variousmethods, including correlation R test, independent t-test, path coefficient, and Cronbach alfa test.